Does Attractiveness and Value of Eco-Tourism Related with Income of Small Medium Micro Business in Tourism Object? Study in North Maluku - Prince Charles Heston Runtunuwu; Zulaiha Husen (AIBPM Publisher, 2023)
The points of this study are: (1) to decide the impact of engaging quality on pay; (2) To decide the impact of ecotourism esteem on pay; (3) To decide the impact of the appeal and worth of ecotourism on pay. The quantity of exploration tests is 70 respondents, This exploration was led at Jikomalamo Ocean side, Ternate City.The test instrument utilized is various direct relapse investigation (different relapse) involving the factual bundle for social researchers (SPSS) as a measurable test device.In view of the exploration results show that; the engaging quality variable emphatically affects the pay of MSME entertainers at the Jikomalamo Ocean side vacation spot, the Ecotourism Worth variable emphatically affects the pay of MSME entertainers at the Jikomalamo Ocean side vacation spot. At the same time, the engaging quality and ecotourism esteem factors emphatically affect pay by 24.3%, and that implies that the allure and worth of ecotourism will build the pay of MSME entertainers at the Jikomalamo Ocean side vacation destination.